A study on optimization methods for solving course timetabling problem in university - Mazlan, Munirah; Makhtar, Mokhairi; Firdaus Khair Ahmad Khairi, Ahmad; Afendee Mohamed, Mohamed; Nordin Abdul Rahman, Mohd (International Journal of Engineering and Technology, 2018)
Course timetabling is one of the most important processes faced by any educational institution. However, the course timetabling process is time consuming and tiresome as it needs to be done for each regular semester. This paper aims to study on the Optimization methods to solve the course timetabling problem. The study is obtained and discussed by categorizing between the classification of Hard Constraint and Soft Constraint and the classification of Optimization Methods. From the study, it shows that Meta-Heuristics are the mostly method used in solving the course timetabling problem. It is concluded that this method is suitable for future used compared to other techniques studied. An analysis and observation will be carried out for the research future.Â Â